Respostas
respondido por:
0
4x -28 = 6x -54 +60 4x -28=6x +6 4x -6x =+6 +28 -2x = 34 34/-2 = -17
respondido por:
0
Vamos lá :
4.(x - 7) = 6(x - 9) + 60
4x - 28 = 6x - 54 + 60
4x - 28 = 6x + 6
6x + 6 = 4x - 28
6x - 4x = - 28 - 6
2x = - 34
x = - 34/2
x = - 17
Espero ter ajudado !!!
4.(x - 7) = 6(x - 9) + 60
4x - 28 = 6x - 54 + 60
4x - 28 = 6x + 6
6x + 6 = 4x - 28
6x - 4x = - 28 - 6
2x = - 34
x = - 34/2
x = - 17
Espero ter ajudado !!!
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás